Răspuns :
Explicație pas cu pas:
[tex] \bf 5^{5}: 5^{2} \cdot(55^{1} - a :5) = 5^{3} [/tex]
[tex]\bf 5^{5 - 2} \cdot(55 - a :5) = 125 [/tex]
[tex]\bf 5^{3} \cdot(55 - a :5) = 5^{3} \: \: \: \bigg| : 5^{3} [/tex]
[tex]\bf 5^{3 - 3} \cdot(55 - a :5) = 5^{3 - 3} [/tex]
[tex]\bf 5^{0} \cdot(55 - a :5) = 5^{0} [/tex]
[tex]\bf 1 \cdot(55 - a :5) = 1[/tex]
[tex]\bf 55 - a :5= 1[/tex]
[tex]\bf 55 = 1 + a :5 \: \: \: \: \bigg| \cdot5[/tex]
[tex]\bf 55 \cdot5= 5 + a[/tex]
[tex]\bf 275= 5 + a[/tex]
[tex]\bf a = 275 - 5 [/tex]
[tex] \red{\bf \underline{ \: a = 270 \: }}[/tex]
[tex] = = pav38 = = [/tex]
[tex]\it 5^5:5^2+5(55-a:5)=5^3 \Rightarrow 5^3+5(55-a:5)=5^3|_{-5^3} \Rightarrow \\ \\ \\ 5(55-a:5)=0 \Rightarrow 55-a:5=0 \Rightarrow a:5=55 \Rightarrow a=55\cdot5 \Rightarrow a=275[/tex]